Democratic Legitimacy of Regional Head Elections by the DPRD from a Constitutional Perspective - Auliaurrahman Auliaurrahman; Nur Anshari (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the selection of regional heads as part of the regional government system should reflect the principle of popular sovereignty and democratic legitimacy as mandated by the 1945 Constitution of the Republic of Indonesia. In reality, however, the election of regional heads by the Regional People’s Representative Council (DPRD) often generates debate regarding its democratic legitimacy, particularly due to limited direct public participation, the dominance of political elites, and transactional political practices that may undermine public trust. This situation raises constitutional questions regarding the extent to which elections conducted by the DPRD can be democratically justified. This study aims to analyze the democratic legitimacy of regional head elections by the DPRD from a constitutional perspective, especially in relation to the principle of popular sovereignty and Article 18 paragraph (4) of the 1945 Constitution. The research employs a library-based qualitative approach using a normative juridical method. The analysis focuses on constitutional norms, statutory regulations, legal doctrines, and relevant Constitutional Court decisions. The findings indicate that normatively, the election of regional heads by the DPRD possesses democratic legitimacy as a form of representative democracy. However, substantively, such legitimacy depends on strengthening accountability and transparency to ensure alignment with the spirit of popular sovereignty.